(untitled) (Cambridge, 2001)
This book brings together scientists working on supernovae and gamma-ray bursts to explore this connection and forge a new understanding. It includes invited reviews by leading experts in both fields who gathered at the Space Telescope Science Institute. It provides a comprehensive review of observations (ranging from gamma-rays to the radio) and theoretical models of supernovae and gamma-ray bursts, and a fascinating exploration of the possible links between the two classes of objects. It also critically examines the use of Type Ia supernovae for measuring the size of the Universe, and recent evidence for a cosmological constant. This volume provides a unique and stimulating reference for all students and researchers interested in supernovae, gamma-ray bursts, and the relationship between them.
Keywords: Supernovae,Gamma ray bursts,Siêu tân tinh,Sự nổ tia Gamma